Feasibility study to inform the design of a UK multi-centre randomised controlled trial of prophylactic antibiotics for the prevention of recurrent cellulitis of the leg - Thomas, Kim S.; Cox, Neil H.; Savelyich, Boki S.P.; Shipley, Debbie; Meredith, Sarah; Nunn, Andrew; Williams, Hywel C.; Reynolds, Nick (Biomed Central, 2007)
Background: This paper describes the results of a feasibility study for a randomised controlled trial (RCT).